Farmer Producer Organizations as Solar Entrepreneurs: The Case for Solar Pumps as Business Investments - Verma, Shilp; Murmu, S.; Kuriachen, Philip; Kumar, D.; Bhattacharjee, Suchiradipta; Usadadia, Nikunj; Mahto, Bhawani Shankhar (International Water Management Institute, 2025)
This brief presents an action research pilot in Kuyani village of Jharkhand, India, implemented jointly by Collectives for Integrated Livelihood Initiatives (CInI) and a local Farmer Producer Organization (FPO), with support from the IWMI-Tata Water Policy Program and the Solar Energy for Rural Livelihoods (SE4RL) project. The objective is to reduce entry barriers and enable small and marginal farmers to benefit from solar-powered irrigation. This innovative business model tests the theory that deploying solar pumps and offering solar irrigation as a service to member farmers would make a good business investment for FPOs. By enabling member farmers to shift from expensive diesel-based irrigation, the model improves agricultural productivity – positively affecting the FPO’s core business activity – and enables improved access and livelihoods for small and marginal farmers. The pilot offers useful field evidence and insights for India’s growing number of FPOs to consider investing in solar irrigation systems.